Dianthus superbus as a critically endangered species in Latvia: evaluation of its growth conditions and conservation possibilities. Issue 5 (7th August 2021) - Osvalde, Anita; Jakobsone, Gunta; Akmane, Ieva; Svilāns, Andrejs; Dubova, Ilze
Abstract: Dianthus superbus is one of the most endangered species in Latvia and is on the verge of local extinction. Therefore, the aim of this study was to inventory previously identified populations of D. superbus in Latvia and to develop activities to conserve this species in accordance with the results obtained in situ . Expeditions on 18 previously documented locations, according to the data of Nature Conservation Agency, revealed only three existing D. superbus localities in Latvia with a significant number of specimens located in the Latgale region near Silenieki. In 2020, for the first time, two more new D. superbus localities were found in the vicinity of these three approved locations. As it is not possible to create micro-reserves in the existing localities which are mainly located either on roadsides or in a cemetery, additional activities are needed to preserve the D. superbus in Latvia. In vitro culture was initiated from shoot explants obtained in situ, from which, in turn, ex vitro plantings were done in the National Botanic Garden (NBG) and the Botanical Garden of the University of Latvia (BG UL). Their quality and compliance with plants in situ were analysed. Overall, it was concluded that the plants grown ex situ were qualitatively equivalent to those obtained in situ, as a very high percentage of seed viability and germination was found both for in situ and ex situ growing D. superbus . Based on the results obtained we could conclude that D. superbus is a species that is able to adapt to different soils with a wide range of nutrient levels, moisture conditions and pH, as long as there are three main preconditions—adequate lighting, low overgrowth of other plant species and non-destructive human activities. Abstract : Ex situ conservation of the critically endangered species Dianthus superbus in Latvia outside natural habitats was carried out by introducing and maintaining in vitro collections and field plantings in the botanical gardens. As D. superbus is able to adapt to a wide range of soil conditions in terms of nutrient and organic matter content and soil reaction, the conservation of this species can also be implemented inter situs in urban areas and dendrological parks. There are three main preconditions for the successful growth of D. superbus in Latvia—adequate lighting, low overgrowth of other plant species and non-destructive human activity.